(untitled) (Pokhara Engineering College Journal, 2026)
Seismic performance of structures is highly influenced by building configuration and the design code adopted. Irregular buildings, especially those with L-, C- and E-shaped plans, are known to exhibit complex dynamic behavior compared to regular-shaped structures. This study focuses on evaluating the seismic response of such irregular configurations using two widely adopted design standards: NBC 105:2020 (Nepal) and IS 1893:2016 (India). A comparative analysis was conducted through equivalent static method using ETABS software, assessing key parameters such as lateral displacement, inter-storey drift, and torsional irregularity. Four different building models—regular, L-shaped, C-shaped, and E-shaped—were analyzed under identical loading, material, and geometric conditions. The results revealed that irregular buildings consistently exhibited higher lateral displacement and drift, particularly at the re-entrant corners where stress concentrations were most severe. Among the codes, NBC 105:2020 produced notably higher drift values in all configurations compared to IS 1893:2016, indicating a more conservative approach. Torsional irregularities were also more pronounced in L- and C-shaped buildings under NBC, due to its stricter consideration of eccentricity and mass irregularity. Overall, the study highlights the critical impact of both structural configuration and seismic code selection on the response of buildings. It is concluded that while NBC 105:2020 provides a higher margin of safety, especially for irregular buildings, careful consideration of building geometry during the design phase remains essential for seismic resilience. The findings underscore the need for enhanced code-specific design provisions for irregular structures in high-seismic zones.